Closed-loop Inventory Routing Problem for Perishable Food with Multi-type Returnable Transport Items. Issue 10 (2022) - Zhang, Yipei; Chu, Feng; Che, Ada
Abstract: This paper studies a multi-period closed-loop inventory routing problem for perishable food that are carried by returnable transport items (RTIs) of different types. We formulate the problem as an integer linear programming (ILP) model considering RTIs with different food quality preserve ability, and the simultaneous delivery of food and pick-up of RTIs. The objective is to maximize the total profit of the holistic supply chain that equals to the selling revenue minus the summation of production, routing, inventory and RTI purchase costs. The proposed model is demonstrated to be correct and effective by conducting computational experiments on randomly generated instances.